Pilot Plant Scale Manufacture of Bread Enriched with Seed Protein Concentrates - Özgenur Coşkun; Halime Pehlivanoğlu; İbrahim Gülseren (Turkish Journal of Agriculture: Food Science and Technology)
For many seeds, cold press technology generates higher quantities of cakes than seed oils, which are concentrated in proteins. Valorization of the cakes could offer a viable strategy to manufacture protein fortified foods with comparable characteristics as the conventional products. Here, black cumin, grape seed and pumpkin seed protein concentrates were prepared based on an alkaline extraction-isoelectric precipitation technique. The influence of protein concentrate addition on the flour, dough and bread characteristics were investigated for textural profile, gluten quality and visual characteristics including color attributes. While the interactions between gluten and seed proteins were mostly weak, some of the physicochemical attributes differed significantly. In terms of volume and visual characteristics, pumpkin seed protein concentrates enriched bread demonstrated similar characteristics as the controls, while black cumin or grape seed protein concentrate enriched wheat flours were more resistant and less extensible than the controls. Similarities and differences between controls and protein enriched gluten-free or gluten-bearing bread were discussed.